2023
DOI: 10.21203/rs.3.rs-3146976/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Mobile Banking Adoption on the Technical Efficiency of Commercial Banks in Ethiopia: An Analysis from 2010 to 2022

Abstract: The study investigates the relationship between mobile banking adoption and the technical efficiency of commercial banks in Ethiopia. The research utilizes a stochastic frontier model and analyzes data from 2010 to 2022. Descriptive statistics, pairwise correlations, and regression analysis are employed to examine the impact of mobile banking on technical efficiency. The findings reveal a small but significant positive effect of mobile banking on technical efficiency, aligning with previous literature highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Studies have identified key drivers of mobile banking adoption, including global mobile phone penetration, competitive advantage, customer convenience, strategic importance, customer demand, low perceived risk/security concerns, and stakeholder partnerships (Zhang et al, 2018). Additionally, the convenience and accessibility of mobile banking have been emphasized as potential factors bridging the banking divide in rural communities, contributing to financial inclusion (Hordofa, 2023). Furthermore, the impact of COVID-19 has highlighted the significance of mobile banking as a contactless financial inclusion tool during the pandemic (Zeya, 2022).…”
Section: Key Technologies Driving Financial Inclusionmentioning
confidence: 99%
“…Studies have identified key drivers of mobile banking adoption, including global mobile phone penetration, competitive advantage, customer convenience, strategic importance, customer demand, low perceived risk/security concerns, and stakeholder partnerships (Zhang et al, 2018). Additionally, the convenience and accessibility of mobile banking have been emphasized as potential factors bridging the banking divide in rural communities, contributing to financial inclusion (Hordofa, 2023). Furthermore, the impact of COVID-19 has highlighted the significance of mobile banking as a contactless financial inclusion tool during the pandemic (Zeya, 2022).…”
Section: Key Technologies Driving Financial Inclusionmentioning
confidence: 99%